Joint Assessment of the Institutional Effectiveness of UNDP - Programme des Nations Unies pour le Développement (United Nations, 2017)
Recognizing that institutional effectiveness is important to both UNDP’s audit and evaluation functions, the Directors of IEO and Office of Audit and Investigations (OAI) undertook the Assessment of UNDP’s Institutional Effectiveness jointly, using both audit and evaluation methods. The UNDP Evaluation Policy and OAI Charter share the same purpose of supporting UNDP through oversight, review of governance, risk management practices and institutional learning. This Assessment report encompasses the joint findings and conclusions of the two offices for presentation to the Executive Board in 2017. The objective of this evaluation is to assess the extent to which policy and organizational measures, including the associated restructuring process, have enhanced or have the potential to enhance UNDP’s ability to deliver higher quality programmes and UNDP’s institutional effectiveness.